Conserved histidine and tyrosine determine spectral responses through the water network in Deinococcus radiodurans phytochrome - Lehtivuori Heli; Rumfeldt Jessica; Mustalahti Satu; Kurkinen Sami; Takala Heikki (SPRINGERNATURE, 2022)
Phytochromes are red light-sensing photoreceptor proteins that bind a bilin chromophore. Here, we investigate the role of a conserved histidine (H260) and tyrosine (Y263) in the chromophore-binding domain (CBD) of Deinococcus radiodurans phytochrome (DrBphP). Using crystallography, we show that in the H260A variant, the missing imidazole side chain leads to increased water content in the binding pocket. On the other hand, Y263F mutation reduces the water occupancy around the chromophore. Together, these changes in water coordination alter the protonation and spectroscopic properties of the biliverdin. These results pinpoint the importance of this conserved histidine and tyrosine, and the related water network, for the function and applications of phytochromes.